Determinan Profitabilitas Bank: Suatu Studi pada Bank yang Terdaftar di BEI - Jaja Suteja; Gerinata Ginting (TRIKONOMIKA, 2014)
This research is aimed at providing empirical evidence of the impact of non interest income, Non Interest Expense, Loan Loss Provisions, Equity, Total Assets, GDP, Market Capitalization on ROA. This research sampled 20 banks listed in Indonesia Stock Exchange during the research period that is 2003 to 2011. Data were analyzed using multiple regression method. Based on the result of analysis, it is concluded that Non Interest Income, Non Interest Expense, Loan Loss Provisions, Equity, Total Assets, GDP, Market Capitalization have significant effect on ROA.